2015
DOI: 10.1016/j.yfrne.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal change in the avian hippocampus

Abstract: The hippocampus plays an important role in cognitive processes, including memory and spatial orientation, in birds. The hippocampus undergoes seasonal change in food-storing birds and brood parasites, there are changes in the hippocampus during breeding, and further changes occur in some species in association with migration. In food-storing birds, seasonal change in the hippocampus occurs in fall and winter when the cognitively demanding behaviour of caching and retrieving food occurs. The timing of annual ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 120 publications
(138 reference statements)
2
32
1
Order By: Relevance
“…This may be analogous to the larger hippocampal volumes seen in food caching birds compared to nonfood caching birds (342,566). The reader is directed to several reviews dedicated to the relation between hippocampal volume and spatial ability (565,680).…”
Section: Hippocampal Functionmentioning
confidence: 81%
“…This may be analogous to the larger hippocampal volumes seen in food caching birds compared to nonfood caching birds (342,566). The reader is directed to several reviews dedicated to the relation between hippocampal volume and spatial ability (565,680).…”
Section: Hippocampal Functionmentioning
confidence: 81%
“…Different behaviors are likely to be under the control of different brain areas (Wingfield 2015). For example, hippocampus volume is linked to food-storing behavior in bird (Croston et al 2015;Sherry and MacDougall-Shackleton 2015); the size of auditory areas is linked to song learning behavior in bird (Nottebohm 1981;Chakraborty et al 2015); and the size of the forebrain region is link to social behavior (Lipkind et al 2002). A recent study reported the absence of correlation between activity during the novel object stimulation after 41 days of environmental enrichment and neurogenesis in the hippocampus and lateral striatum of adult pigeons (Columba livia) (Melleu et al 2015), suggesting that those two brain areas may not be responsible for variation in activity during exposure to novel objects.…”
Section: Discussionmentioning
confidence: 99%
“…This involves the avian hippocampus and both neurogenesis and neural survival. This food-storing behavior changes markedly with season and is correlated with hippocampal size but it does not appear to be under photoperiod control (Sherry & MacDougall-Shackleton, 2015).…”
Section: Seasonality Within the Brain Itselfmentioning
confidence: 95%